2017
DOI: 10.1017/s0305004117000743
|View full text |Cite
|
Sign up to set email alerts
|

A note on pointwise convergence for the Schrödinger equation

Abstract: We consider Carleson's problem regarding pointwise convergence for the Schrödinger equation. Bourgain recently proved that there is initial data, in H s (R n ) with s < n 2(n+1) , for which the solution diverges on a set of nonzero Lebesgue measure. We provide a different example enabling the generalisation to fractional Hausdorff measure.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 30 publications
1
38
0
Order By: Relevance
“…We then have the following theorem. the best positive and negative results to date are in [18] and [28,29], respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We then have the following theorem. the best positive and negative results to date are in [18] and [28,29], respectively.…”
mentioning
confidence: 99%
“…Using these facts and the Sobolev embedding H 1 2 + (Ω) ֒→ L ∞ (Ω), we see that the (1d analog of) property (8) is satisfied by initial data in H s (Ω) with s > 1/6. On the other hand, in [36] (see also [29]) it has been observed that for any s < 1/4 there are initial data such that lim sup t→0 |e it∆ f (x)| = ∞ for x in a set of strictly positive measure. This construction, done for Ω = R, is based on the Dahlberg-Kenig counterexample and can be repeated also in the periodic setting.…”
mentioning
confidence: 99%
“…In higher dimensions, Sjölin [22], Vega [27], Bourgain [3] and Du-Guth-Li-Zhang [11] made progresses, and recently, Du-Zhang [12] have proven the convergence for the sharp range s > n/2(n + 1) by showing the local maximal K loc (L 2 x L ∞ t ; α) for α < −n/2(n + 1). (For sharpness of the regularity range s, see [2,9,18,19].) (When n = 1 the maximal estimate K loc (L 2 x L ∞ t ; α) for α ≤ −1/4 was already obtained by Kenig-Ruiz [16].…”
Section: Introductionmentioning
confidence: 97%
“…almost everywhere whenever f ∈ H s (R n ). Many authors put a lot of effort on the development of this subject and obtained sharp or partial pointwise convergence results for various P (ξ), see the related works [1][2][3], [5], [8], [14][15][16][17][18], [19,20], [22][23][24][25][26][27][28][29][30], [32], [34][35][36][37][38][39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%